Answer:
7ygfce
Step-by-step explanation:
Answer:
The equation 'y = y + 1' represents NO SOLUTION.
Hence, option 'C' is true.
Step-by-step explanation:
a)
6a = 9a
subtract 9a from both sides
6a - 9a = 9a - 9a
-3a = 0
divide both sides by -3
-3a / -3 = 0/-3
Simplify
a = 0
b)
5x = 28
divide both sides by 5
5x/5 = 28/5
x = 28/5
c)
y = y + 1
subtract y from both sides
y - y = y+1-y
0 = 1
These sides are not equal, so
NO SOLUTION!
d)
y + 5 = 12
subtract 5 from both sides
y + 5 - 5 = 12 - 5
y = 7
Conclusion:
Therefore, the equation 'y = y + 1' represents NO SOLUTION.
Hence, option 'C' is true.
Answer:
x - 3/7
Step-by-step explanation:
Answer:
y = (5-2x)/7 = 5/7 - 2x/7. option C
Step-by-step explanation:
here's your solution
=> 7y + 2x = 5
=> 7y = 5 - 2x
=> y = (5-2x)/7
